2009
DOI: 10.1002/art.24998
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of functionally active CD20+ T cells by rituximab treatment

Abstract: Objective. Rituximab is a therapeutic anti-CD20 antibody used for in vivo depletion of B cells in proliferative and autoimmune diseases. However, the mechanisms of action are not fully understood, since not all of the therapy-mediated effects can be explained by the depletion of antibody-secreting cells. In addition to B cells, there is also a small population of T cells coexpressing CD20 in all individuals. This study was conducted to examine the phenotype and function of CD3؉CD20؉ T cells in patients with rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
134
2
7

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(155 citation statements)
references
References 25 publications
12
134
2
7
Order By: Relevance
“…We first characterized the phenotype of these T cells in peripheral blood mononuclear cells (PBMCs) from 28 normal donors (mean Ϯ SEM age 44.6 Ϯ 8.3 years [range 28-58]) and found, consistent with the reports by Wilk et al (1) and others (2,7,8), that CD3ϩCD20ϩ cells were present in the peripheral blood of normal donors, at frequencies ranging from 0.11% to 5.7% in our study (mean Ϯ SEM 2.2% Ϯ 0.4%), with no correlation with donor age. Using samples from 10 normal donors, we compared the marker frequencies of such…”
Section: To the Editorsupporting
confidence: 84%
See 1 more Smart Citation
“…We first characterized the phenotype of these T cells in peripheral blood mononuclear cells (PBMCs) from 28 normal donors (mean Ϯ SEM age 44.6 Ϯ 8.3 years [range 28-58]) and found, consistent with the reports by Wilk et al (1) and others (2,7,8), that CD3ϩCD20ϩ cells were present in the peripheral blood of normal donors, at frequencies ranging from 0.11% to 5.7% in our study (mean Ϯ SEM 2.2% Ϯ 0.4%), with no correlation with donor age. Using samples from 10 normal donors, we compared the marker frequencies of such…”
Section: To the Editorsupporting
confidence: 84%
“…Wilk et al recently reported findings suggesting that rituximab treatment in rheumatoid arthritis is associated with depletion of a small T cell subset expressing the CD20 B cell marker (1). Expression of the CD20 molecule by leukemic T cells has been demonstrated by immunohistochemistry (2-6), raising the question of whether these leukemic cells resulted from abnormal expression occurring during the malignant transformation process, or whether they resulted from the transformation of a small CD20ϩ T cell subset existing at a normal state.…”
Section: To the Editormentioning
confidence: 99%
“…The non-significant drop in T-cell counts may be due to the recently reported expression of CD20 in a small subpopulation of the CD3 + T-cell pool. 34 The previously reported increased lysis of erythrocytes in the presence of the C terminal fH domain was observed when the classical pathway was blocked by Mg-EGTA, suggesting the involvement of the alternative complement pathway. 31 In our approach it is most likely that the initial complement activation occurs via the classical pathway, as in the absence of ofatumumab no cell lysis and no presence of the active C3 α' chain was observed.…”
Section: Discussionmentioning
confidence: 88%
“…A T-sejtek kb. 6%-án kimutatható CD20 expresszió [10], és a memóra típusú CD4 + Tsejtek kialakulásában, érésében a B-sejtek antigén prezentálásának is valószínű a szerepe [11].…”
Section: Ezek Alapján Határoztuk El Hogy Felmérjük a Klinikánkon 200unclassified